Enhancing creativity, achievement and attitude towards science through computers among primary four gifted pupils - Ng, Li Khoon. (2008)
The purpose of this study is to investigate whether the use of computers could enhance creativity among Primary 4 gifted pupils in Science, encompassing both general creativity and creativity in science. This study also explores the relationship between the two and whether attitude towards Science and achievement in Science would be enhanced in the process of using computers.